One health approach in Nepal: Scope, opportunities and challenges - Acharya, Krishna Prasad (One Health, 2019)
One Health (OH) is a collaborative effort to attain optimal health for people, animals and the environment. The concept of OH is still in its infancy in Nepal but is increasingly growing. The Government of Nepal (GoN) has taken some initiatives to tackle burgeoning problems such as antimicrobial resistance, highly pathogenic avian influenza and rabies using OH approach but there are several challenges at the level of implementation. Few non-governmental organizations support GoN to promote an OH approach. The major bottlenecks in implementing OH in Nepal include poor organizational structure to support OH, absence of a legal framework to implement OH, poor coordination among different governmental agencies, insufficient technical expertise, poor data sharing mechanism across sectors, limited budget and poor understanding at political level. We encourage GoN to address these gaps and prioritize the health problems where OH approach would give the best outcome. Institutional and legal frameworks need to be created to effectively implement an OH approach in Nepal. Increasing awareness among policy makers including political leadership and increasing regular government budget for OH activities would be helpful to promote OH in Nepal.